Mr. Bolsonaro and the Chinese: a suggested interpretation - Libânio, Gilberto (Brazilian Keynesian Review, 2019)
This paper aims to discuss the potential impacts of Jair Bolsonaro’s government on Brazil-China relations. Firstly, it presents the recent history of relations between the two countries, particularly in regards to international trade and to Chinese FDI (foreign direct investment) in Brazil. Secondly, the paper speculates on the potential effects of a detachment of Brazil from China, in case the recurrent discourse of members of the new government, including the new president, is put into practice, regarding a political realignment with the USA and a consequent distancing of the Asian giant. The main conclusion of the article is that China plays a crucial role in Brazil’s foreign economic relations and that there’s no justification for any kind of disruption in this relationship, due to the risk of negative effects on Brazli’s trade balance and reception of foreign investments.